Bactericidal vertically aligned graphene networks derived from renewable precursor. (April 2022) - Al-Jumaili, Ahmed; Zafar, Muhammad Adeel; Bazaka, Kateryna; Weerasinghe, Janith; Jacob, Mohan V.
Abstract: Graphene nanostructures exhibit a wide range of remarkable properties suitable for many applications, including those in the field of biomedical engineering. In this work, plasma-enhanced chemical vapor deposition was utilized at different applied RF power for the fabrication of vertical graphene nanowalls on silicon and quartz substrates from an inherently volatile carbon precursor without the use of any catalyst. AFM confirmed the presence of very sharp exposed graphene edges, with associated high surface roughness. The hydrophobicity of the material increased with the power of deposition, reaching the water contact angle of 123 ˚ for 500 W. Confocal scanning laser microscopy demonstrated that the viability of gram-negative Escherichia coli and gram-positive Staphylococcus aureus cells were 33% and 37% when incubated on graphene samples, respectively, compared to controls (quartz) that showed the viability of 82% and 84%, respectively. SEM verified significant morphological damage to bacterial cell walls by the sharp edges of graphene walls, with cells appearing abnormal and deformed. The presented data clearly contributed to the current understanding of the mechanical-bactericidal mechanism of vertically oriented graphene nanowalls upon direct contact with microorganisms.